Language teaching linguistic theory in practice - Whong, Melinda; IG Publishing (Edinburgh Edinburgh University Press, 2011)
How can theories of language development be understood and applied in your language classroom? By presenting a range of linguistic perspectives from formal to functional to cognitive, this text highlights the relevance of second language acquisition research to the language classroom.
Introduction -- Historical overview : language and language teaching -- Language as a biological property -- Language as tool for communication -- Implications for language teaching -- Approaches to English language teaching -- Putting theory into practice -- Practice and practices : responding to student needs.
Electronic reproduction.
Keywords: Language and languages -- Study and teaching; Linguistics; Electronic books